POLITICS AND THEATER (Heritage, 2023)
The subject of this scientific paper is the indispensable connection between politics and theater, their interdependence in social and political relations. In a given country, without people, or more precisely, without actors who represent them in a theatrical performance, there is no history, no politics, no culture, no theater, and no political events in a certain time, space and territory. Political events from the recent or distant past are often the subject of staged plays. Such theater becomes political theater. Through the performance, the theater can perceive certain subjects, in specific situations, and solve their problems in their own way, as well as critically explain and interpret them, from the aspect of results, effects and consequences. In the paper, the authors indicate the distinction between Aristotle's theater and Brecht's theater, which is manifested in their different function and relationship to the state. Namely, Aristotle's theater supports the existing state order as a divine order, while Brecht destroys the state order through theater. Brecht's theater becomes a political theater, its role is to awaken and change the consciousness of the audience and to convert it in the direction of an ideology, which as such will make its contribution to the state.
Keywords: politics, political force, state, political theater, theater, Aristotle, Brecht, violence, power.